Uma história da educação: A invenção da instrução pública na província do Ceará (1858-1889) - Silva, Bárbara Eliza Soares (2012)
This research takes as propose tell how the public instruction in the Province of Ceara was made. It will be analyzed documentation that was produced by ‘Instruçao Publica’, a public institution in the Provincial Govern responsible for the education at Ceara. This extensive documentation, that is present in the Public Archives of the State of Ceará, is made up of complaints against teachers who worked in public education during the period analyzed. The period of study in this research is bounded by the appearance of complaints against teachers, in 1858th, and the date of the results of the last complaint, in 1889th. We tried to make the conection between the Presidents Reports of the Province of Ceara, the laws created for the instruction in the Brazilian Empire and the Province, novels, short stories and poems related to the topic of education. The period studied is guided by the discussions about what and who should be taught; boundaries on relations within the school and which models would be used otherwise for the organization of education in the Province.